Sex differences in the effects of transcranial direct current stimulation on attentional bias to alcohol - Pang, Nicole Wan Joo (Nanyang Technological University, 2020)
Attentional bias to alcohol cues has been a factor that has been widely explored empirically as one of the motivations for the maintenance of alcohol consumption. There has, however, been little research in an Asian context, and present interventions for alcohol-related issues have also largely been of a psychosocial basis. This randomised, placebo-controlled trial hence examines the effects of transcranial direct current stimulation (tDCS), a non-invasive intervention, on participants’ attentional bias to alcohol cues in a subsample (n = 32) taken from a larger ongoing study. Participants either went through active or sham stimulation, and between-group comparisons were made with regard to their attentional bias to alcohol cues. The attentional bias to alcohol cues was assessed using an alcohol dot-probe task. Results revealed that participants who went through active stimulation had lower attentional bias to alcohol cues as compared to those who had received sham stimulation, although results were not statistically significant. Active stimulation largely reduced the attentional bias to alcohol cues in males but not in females, albeit once again not statistically significant. Mechanisms underlying the relationship between tDCS and attentional bias to alcohol cues were theorised and discussed. Differential social norms between sexes in the Singaporean context were also explored to provide a plausible explanation for the findings. The paper ends with several limitations and areas for future research.